2018
DOI: 10.1073/pnas.1800656115
|View full text |Cite
|
Sign up to set email alerts
|

Repression of human and mouse brain inflammaging transcriptome by broad gene-body histone hyperacetylation

Abstract: Brain "inflammaging," a low-grade and chronic inflammation, is a major hallmark for aging-related neurodegenerative diseases. Here, by profiling H3K27ac and gene expression patterns in human and mouse brains, we found that age-related up-regulated (Age-Up) and down-regulated (Age-Down) genes have distinct H3K27ac patterns. Although both groups show promoter H3K27ac, the Age-Up genes, enriched for inflammation-related functions, are additionally marked by broad H3K27ac distribution over their gene bodies, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 40 publications
3
47
0
1
Order By: Relevance
“…Transcriptome datasets of 591 pre-frontal cortex biopsies measured on several Affymetrix microarray platforms and via rnaSeq (Illumina HiSeq) were downloaded from NCBI GEO (Supplementary Table 1). These datasets originate from studies by Narayan et al [41], Barnes et al [4], Lu et al [36], Lanz et al [34], Chen et al [10], Hagenauer et al [24] and Cheng et al [11]. Table 1 shows the distribution of the datasets between female and male samples and over age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome datasets of 591 pre-frontal cortex biopsies measured on several Affymetrix microarray platforms and via rnaSeq (Illumina HiSeq) were downloaded from NCBI GEO (Supplementary Table 1). These datasets originate from studies by Narayan et al [41], Barnes et al [4], Lu et al [36], Lanz et al [34], Chen et al [10], Hagenauer et al [24] and Cheng et al [11]. Table 1 shows the distribution of the datasets between female and male samples and over age groups.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic alterations found during aging seem to depend on the residue modified within a histone and the position of the histone mark along the targeted gene or within the genome. For example, by RNA‐seq analysis, Cheng et al identified two sets of age‐regulated genes in PFC of both human and mouse: an age‐downregulated group mainly involved in neural function and an age‐upregulated group enriched in genes with inflammation‐related functions (Cheng et al, ). These results show that, whereas the levels of acetylated H3 lysine 27 (H3K27ac) were reduced with aging in the promoters of both groups of genes, significantly decreased H3K27ac levels were observed at the gene bodies of upregulated genes.…”
Section: Histone Post‐translational Modificationsmentioning
confidence: 99%
“…These results show that, whereas the levels of acetylated H3 lysine 27 (H3K27ac) were reduced with aging in the promoters of both groups of genes, significantly decreased H3K27ac levels were observed at the gene bodies of upregulated genes. These results suggest that broad gene‐body H3K27 acetylation would suppress rather than activate gene expression and that H3K27 deacetylation at gene bodies would lead to transcriptional activation of pro‐inflammatory genes (Cheng et al, ).…”
Section: Histone Post‐translational Modificationsmentioning
confidence: 99%
“…Protein lysine acetylation (Kac) is a conserved posttranslational modification that links acetyl-coenzyme A metabolism, including histone and non-histone acetylation (Shakespear et al, 2011). Protein posttranslational acetylation and deacetylation processes are factors in many human diseases and vital development, including neurodegenerative diseases, nerve system development, pulmonary fibrosis, neuroprogenitor survival and proliferation, neuronal maturation, maturation of astrocytes inflammation, and immunity in vertebrates (Sun et al, 2013;Choudhary et al, 2014;Li et al, 2017;Cheng et al, 2018). Numerous studies proved that the immune response was different from organ to organ (Sun et al, 2014;Tapias and Wang, 2017).…”
Section: Introductionmentioning
confidence: 99%